1998
DOI: 10.1007/s003390051204
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of fixed and living liver endothelial cells by atomic force microscopy

Abstract: We have investigated living and glutaraldehyde fixed liver endothelial cells (LEC) by atomic force microscopy (AFM). In living cells, resolution is generally poor compared with what we have found with the same cells after fixation. LECs possess arrays of pores or fenestrae in their membrane, grouped in so-called sieve plates. In living cells these sieve plates could not be resolved by AFM. However, they could be picked up easily in fixed cells. The size of these fenestrae is around 200 nm. The difference in re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
96
1

Year Published

1998
1998
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 122 publications
(107 citation statements)
references
References 20 publications
10
96
1
Order By: Relevance
“…The atomic force microscope can be easily operated under physiological conditions (25) and has the potential to monitor dynamic cellular events at nanometer resolution in real-time (26). Studies with the atomic force microscope on living LSECs are underway (27) to check our hypothesis on the translocation of preexisting FFC in realtime.…”
Section: Discussionmentioning
confidence: 99%
“…The atomic force microscope can be easily operated under physiological conditions (25) and has the potential to monitor dynamic cellular events at nanometer resolution in real-time (26). Studies with the atomic force microscope on living LSECs are underway (27) to check our hypothesis on the translocation of preexisting FFC in realtime.…”
Section: Discussionmentioning
confidence: 99%
“…glutaraldehyde, that cross-link proteins at the cell surface, thereby ''freezing'' the morphology of the cell. For liver endothelial cells typical values of the elastic modulus are around 2 kPa for the living cell and more than 100 kPa for the glutaraldehyde fixed cell [935] and for E. coli K12 strains a 4 fold increase of cell stiffness due to fixation was found [936].…”
Section: Filled Polyelectrolyte Capsulesmentioning
confidence: 99%
“…We found that the measured apparent mass is 1.4 times greater for paraformaldehyde (PFA)-fixed cells than for the corresponding live cell, which demonstrates that indeed the measured apparent mass is a function of the stiffness of target cells. It is well-known that fixation of tissue samples increases their stiffness as compared to fresh, unfixed tissues (26,27), and causes a minor (∼3%) shrinkage in volume (28). Hence, we assumed that the fixation process does not introduce any additional confounds in the measurement and subsequent analysis.…”
Section: Interplay Between Cell Stiffness and Cell Mass Measurementsmentioning
confidence: 99%